Effect Of Tax Amnesty Law On Waqf - Budi Prajogo; Siti Choiriah; Sukiranto Sukiranto (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2017)
Tax Amnesty Law is the breakthrough success of the government to increase tax revenues as well as strengthen the database taxation. This policy also encourages economic restructuring due to the inflow of funds owned Indonesia citizens who were abroad and within the country but yet was listed as the basis of taxation. Problems arise mostly when Waqf property has not been registered in the yearly tax report until the object is considered part of this Law. Waqf property that has been handed down and has not been reported to the yearly tax report considered as illegal property that must be paid the fine when it registered as tax amnesty, the same as the property obtained from crime. Author made observations on the organization of Islamic organization that has long been managing the waqf. Most can adapt to this Act but some are not ready for this for waqf property is considered not taxed therefore not be registered in the Tax return. Keywords: Tax Amnesty, Endowments, Muhamadiyah, Nahdlatul Ulama